Geometric SMOTE for imbalanced datasets with nominal and continuous features - Fonseca, Joao (2023)
Fonseca, J., & Bacao, F. (2023). Geometric SMOTE for imbalanced datasets with nominal and continuous features. Expert Systems with Applications, 234(December), 1-9. [121053]. https://doi.org/10.1016/j.eswa.2023.121053 --- This research was supported by research grants of the Portuguese Foundation for Science and Technology (“Fundação para a Ciência e a Tecnologia”), references SFRH/BD/151473/2021, DSAIPA/DS/0116/2019, and by project UIDB/04152/2020 — Centro de Investigação em Gestão de Informação (MagIC) .